Time for Punishment with Subjectivity: Study Philosophy of Law - Sulistyawan, Aditya Yuli (Universitas Islam Negeri Walisongo Semarang, 2019)
The dominance of legal positivism in thought and law enforcement is a reality. Saintism of legal science presents a law that is conceptualized as something that exists in sensory terms, along with its straightforward, rational, and objective nature. Law is always requested objectively. Objectivity is done by freeing the subject's mind to the legal reality that already exists as an object. Therefore, various legal cases such as the case of Asyani, Rasminah, Minah and others, are things that are easily proven as violating the law because it is a violation of the text of the article of law. Such a way of law, is now starting to become a public concern. So, when objectivity begins to be questioned, that's when the real subjectivity of asking begins to be considered - and this will be explained [only] in the study of legal philosophy, especially paradigmatic studies. This paper will discuss the possibility of subjectivity in law, which will be presented in the paradigmatic study.